High‐resolution temporal dynamics of intra‐storm isotopic composition of stemflow and throughfall in a Mediterranean Scots pine forest. Issue 8 (30th July 2022) - Pinos, Juan; Llorens, Pilar; Latron, Jérôme
Abstract: Vegetation plays a significant role in the isotopic fractionation of rainwater during rainfall partitioning through the canopy into throughfall and stemflow. Most studies focus on the isotopic composition of throughfall, whereas that of stemflow has been studied much less frequently. Moreover, only three studies to date have investigated stemflow isotopic composition at the intra‐storm scale. Therefore, knowledge of the isotopic shift between rainfall and throughfall/stemflow at fine resolutions is sorely needed in order to better understand water input to forest soils. In this study, intra‐event rainfall, throughfall and stemflow in a Scots pine forest under Mediterranean conditions were monitored (5‐min time step) over a 20‐month period (May 2018 to December 2019) and water samples of each component were collected sequentially by means of automatic samplers for isotopic analysis ( 18 O and 2 H). Results obtained for 21 rainfall events show that throughfall was usually more enriched than rainfall and stemflow was more enriched than throughfall. Isotopic differences between rainfall and throughfall/stemflow indicated that throughfall was more depleted during the higher air temperature season whereas stemflow was more enriched. The isotopic shift did not show any direct relationship with either meteorological variables or the amount effect. At the intra‐storm scale, stemflow was more enriched than rainfall and throughfall at the start of the rainfall event and tended to decrease towards the end. Our results suggest that evaporation led to stemflow enrichment due to stemflow residing longer on the vegetative surfaces than throughfall. However, most fractionation factors can occur during the same event. Our study will improve understanding of the physical processes that control stemflow isotopic composition in coniferous trees before reaching the ground, as a step towards improving isotope‐based models for forest‐water interactions. Abstract : This study used hydrometric and water stable isotope data to investigate the dynamics of intra‐storm isotopic composition of throughfall and stemflow. We show that isotopic differences between rainfall with throughfall and stemflow can occur in both directions (enrichment or depletion) and are not correlated with meteorological variables or rainfall amount. This study emphasized that isotopic fractionation in throughfall or stemflow is caused by factors such as evaporation, exchange, mixing of waters and canopy selection processes or a combination of them.